(untitled) (Third Sector Social Economic Review, 2026)
This study examines the socio-economic structure of the village of Tivnik (today Altınbulak), located in the Erzurum region, on the basis of the Temettuat Registers dated 1844–1845, and treats the case as a micro-level prototype reflecting the functioning of an agriculture-based rural village economy in the Ottoman provinces. Using household-level data recorded in the registers, the study analyses the population structure, occupations, land ownership, agricultural production, livestock activities, income sources, and tax obligations within an integrated framework. The data employed in the study provide detailed records that enable an assessment of the main dynamics of the village economy in the relevant period. In addition to descriptive analysis, income distribution is measured through quantitative economic methods, namely the Lorenz curve and the Gini coefficient, and the findings are systematically evaluated. Based on total income data for sixty-six households, the Gini coefficient of Tivnik village is calculated as 0.404. This finding indicates that income distribution in the village economy deviates from perfect equality, yet does not reach a level of extreme inequality. Considering the fiscal nature of the temettuat records, the results should be interpreted as approximate indicators rather than absolute measures. In this respect, the study contributes to the literature by demonstrating that the structural characteristics of rural economies in the Ottoman provinces can be analysed at the micro level through temettuat registers.